Into the gray zone - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller, 2025)
"Pike Logan uncovers a geopolitical scheme that has spiraled out of control in India in this latest pulse-pounding thriller from New York Times bestselling author and former special forces officer Brad Taylor"--